Morphological bases of embryonic myocardium trabeculation and compactization - Gorbunov A.A.; Tverdokhleb I.V. (Морфологія, 2008)
The purpose of the current study was the analysis of the very mechanisms of the heart wall trabeculation and compactization, as well as these processes interaction and their morphogenetic role in the development of spatial myocardium organization. The serial sections of the embryonic human and rat myocardium have been processed with standard histological methods. It has been revealed that myocardial compactization is related to the trabecules internal structure rebuilding. Spatial-directional role belongs to the developing capillary network. Proliferation of the endothelal cells growing into trabecules activates proliferation of cardiomyocites. Therefore, vasculogenesis and myocardial compactization, based on cyclic proliferation of cardiomyocytes and endotheliocytes, are the topologically correlated and phase-synchronized processes.